Oil palm expansion among smallholder farmers in Sumatra, Indonesia - Michael Euler; Stefan Schwarze; Hermanto Siregar; Matin Qaim (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2015)
Many tropical regions experience a rapid expansion of oil palm, causing massive land use changes and raising serious environmental and social concerns. Indonesia has recently become the largest palm oil producer worldwide. While much of the production in Indonesia comes from large-scale plantations, independently operating smallholders are increasing in importance and may domi-nate production in the future. In order to control the process of land use change, the micro level factors influencing smallholder decisions need to be better understood. We use data from a survey of farm households in Sumatra and a duration model to analyze the patterns and dynamics of oil palm adoption among smallholders. Initially, smallholders were primarily involved in government-supported out-grower schemes, but since the mid-1990s independently operating oil palm farmers have become much more important. In addition to farm and household characteristics, village level factors determine oil palm adoption significantly. Independent smallholders adopt oil palm especially in those villages that also have contracts and out-grower schemes, leading to a regional path-dependency of former government policies.
urn:nbn:de:gbv:7-webdoc-3946-0
Keywords: 330; Oil palm expansion; Land use change; Indonesia; Duration models; Pflanzenbau; Ölfrucht; Palme; Kleinbauern; Landnutzung; Sumatra; Indonesien